Analisis Terhadap Makna Simbol Budaya Lokal Di Dalam Iklan “ Kuku Bima Ener-G Versi Sumatera Utara” Di Televisi ( Analisis Semiotika Roland Barthes ): Analysis of the Meaning of Local Cultural Symbols in the "Kuku Bima Ener-G North Sumatra Version" Advertisement on Television (Roland Barthes Semiotics Analysis) - Muchammad Akbar Aprillyanto (Journalism, Public Relation and Media Communication Studies Journal (JPRMEDCOM), 2022)
ABSTRACT Advertising is a means of communication used to convey a message from an advertiser to his target audience. One of the advertising media that is effectively used is television. This advantage is utilized by e-commerce companies as advertising media, one of which is Kuku Bima Ener-G. this research is a qualitative descriptive analysis research that focuses on the meaning conveyed in the Kuku Bima Ener-G advertisement. The data used in this study was the Kuku Bima Ener-G television commercial series. the series is famous for its simple but multi-meaning method of advertising delivery. This study aims to explain the meaning of denotations, connotations, and myths contained in the form of sign charts. In addition, this study also aims to find out the meaning of the advertisement you want to convey in the advertisement. This research uses the theory of semiotics according to the perspective of Roland Barthes. The results of this study show that the meaning of the advertisement conveyed by Kuku Bima Ener-G contains a cultural message, Kuku Bima Ener-G as a communicator tries to provide meaning to its consumers in order to better know the local culture in Indonesia which is shown from the meaning of denotation, connotation, and myth contained in this advertising series. Keywords : Semiotics, advertising, Nails Bima Ener-G